Overtopping Performance of a Pier-Type Slope-Ramp Breakwater-Integrated Overtopping Wave Energy Converter: An Experimental Study - Zhen Liu; Guoliang Zhang; Lei Ding; Ziqian Han; Heqiang Ni (Journal of Marine Science and Engineering, 2026)
Overtopping wave energy converters share a similar geometry with traditional slope-ramp breakwaters, allowing integrated development that simultaneously ensures the basic protection function of the structure and realizes wave energy absorption. This study proposes a dual-level overtopping wave energy converter (DULOW) integrated with a pier-type slope-ramp breakwater, specifically designed for oceanic environmental conditions characterized by smaller wave heights and larger tidal ranges. An experimental laboratory investigation was conducted in a wave tank to evaluate the overtopping performance of the DULOW model under regular and irregular wave conditions. The experimental results show that the overtopping discharge increases with the number of plane collectors, and that the discharge collected by the plane collectors is significantly larger than that of the quadrant cone collector. At the higher still water level, the presence of the lower collector reduces the overtopping discharge captured by the high-level collectors. Under irregular wave conditions, the averaged overtopping discharges are lower than those observed under regular wave conditions. Furthermore, a semi-empirical formula is proposed to describe the variation trend of overtopping discharge with effective crest freeboard for the tested DULOW configuration.